2018
DOI: 10.1111/jphp.12896
|View full text |Cite
|
Sign up to set email alerts
|

Glucantime reduces mechanical hyperalgesia in cutaneous leishmaniasis and complete Freund's adjuvant models of chronic inflammatory pain

Abstract: Our data demonstrated that Glucantime reduced the chronic inflammatory pain induced by L. amazonensis and CFA stimuli by inhibiting the hyperalgesic cytokines production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Tissue sections 7 µm thick were stained with hematoxylin and eosin and then observed by light microscopy coupled with an imaging system (Leica DM2000, Milan, Italy). Histopathological damage was calculated using a single-blinded model from observation of 10 different fields of H&E-stained sections from each animal, as seen previously by Cortes et al The histopathological-score grading system used to evaluate the degree of histopathological damage was as follows: 0: none; 1: slight infiltration of inflammatory cell; 2: moderate infiltration; 3: severe infiltration [22]. Myeloperoxidase (MPO) activity, an indicator of neutrophil infiltration, was calculated as previously described [23].…”
Section: Histological Analysis and Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
“…Tissue sections 7 µm thick were stained with hematoxylin and eosin and then observed by light microscopy coupled with an imaging system (Leica DM2000, Milan, Italy). Histopathological damage was calculated using a single-blinded model from observation of 10 different fields of H&E-stained sections from each animal, as seen previously by Cortes et al The histopathological-score grading system used to evaluate the degree of histopathological damage was as follows: 0: none; 1: slight infiltration of inflammatory cell; 2: moderate infiltration; 3: severe infiltration [22]. Myeloperoxidase (MPO) activity, an indicator of neutrophil infiltration, was calculated as previously described [23].…”
Section: Histological Analysis and Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
“…In this study, new potential Sb(V) complexes were identified by combining the benefits of antimony (V) and flavonols and optimizing their properties. The UV, NMR, and ESI analysis confirmed the structure of synthesized compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Among them, QPMB-Sb (11) and QPNB-Sb (12) as newly described, and other compounds as predefined compounds were identified.…”
Section: Discussionmentioning
confidence: 61%
“…The maximum absorbance (λ max ) was determined using UV spectra to determine the end of the reaction. At the end of the series, the reaction medium was air-dried for 24 hours to a fine orange powder and washed with deionized water to remove residue of free SbCl 5 to obtain Sb(V) kaempferol complex (9). Quercetin (2, 20 mg, 0.0662 mmol) in 100 mL anhydrous methanol was the subject of adding SbCl 5 solution (0.033 mmol) in the same way as 9 to obtain Sb(V) quercetin complex (10).…”
Section: Synthesis Of Sb(v) Kaempferol and Quercetin Derivative Compl...mentioning
confidence: 99%
See 1 more Smart Citation